Production and characterization of a new biodegradable fenugreek seed gum based active nanocomposite film reinforced with nanoclays - Memis, Saliha; Tornuk, Fatih; Bozkurt, Fatih; Durak, M. Zeki (ELSEVIER, 2017)
In the present work, fenugreek seed gum (FSG)/clay nanocomposite films were prepared with nanoclays (Na+ montmorillonite [MMT], halloysite [HNT] and Nanomer (R) 1.44P [NM]) at different amounts (0, 2.5, 5.0 and 7.5 g clay/100 g FSG) by solution casting method and characterized. Increasing amount of nanoclay significantly (P<0.05) improved oxygen barrier and thermal properties of the biodegradable films. Agar diffusion tests revealed that FSG based nanocomposite films exhibited strong antimicrobial properties against foodborne pathogens namely Listeria monocytogenes, Escherichia coil O157:H7, Staphylococcus aureus and Bacillus cereus independently of clay type and concentration. In the case of mechanical properties, nanoclay incorporation up to 5% provided higher (P < 0.05) tensile strength (TS) properties while elongation at break (EB) values of the films significantly (P<0.05) decreased in the presence of clay in the film matrix. SEM micrographs showed that especially lower levels (up to 5%) of nanoclay reinforcements provided a homogeneous and smooth film structure. In conclusion, FSG based nanocomposite films reinforced with nanoclays up to 5% showed a precious potential to be used in antimicrobial food packaging applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Nanofiller; Polymer reinforcement; Film properties; ANTIMICROBIAL PROPERTIES; BIO-NANOCOMPOSITES; BARRIER PROPERTIES; EDIBLE FILM; CLAY; POLYSACCHARIDE; CARBOHYDRATE; EXTRACTION; Biochemistry & Molecular Biology; Chemistry; Polymer Science